1991
DOI: 10.1111/j.1365-2125.1991.tb05615.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐related analgesic effects of flupirtine.

Abstract: 1 Flupirtine is a novel and, in all probability, centrally acting, analgesic. The present investigation was conducted in order to investigate dose-related effects of perorally administered flupirtine in man, with special regard to specifically analgesic actions, employing a model based on pain-related chemosomatosensory evoked potentials and subjective intensity estimates of painful stimuli. 2 Plasma concentrations of flupirtine measured 2 h after dosing linearly increased as a function of the administered dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 14 publications
5
38
0
Order By: Relevance
“…This was indicated by the decrease of CSSERP amplitude P2 [16,27,36]. It has previously been demonstrated that event-related potentials represent an objective tool for assessment of pain and analgesic effects [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Thus, our data indicate the presence of analgesic effects of both flurbiprofen enantiomers.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…This was indicated by the decrease of CSSERP amplitude P2 [16,27,36]. It has previously been demonstrated that event-related potentials represent an objective tool for assessment of pain and analgesic effects [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Thus, our data indicate the presence of analgesic effects of both flurbiprofen enantiomers.…”
Section: Discussionmentioning
confidence: 56%
“…Changes in CSSERP amplitudes were found largest with 100 mg (R)-flurbiprofen, which reduced amplitude P2 by 36%. Compared with other analgesics investigated with the same model, the magnitude of this effect was superior to the effects produced by 800 mg ibuprofen [25] and 1000 mg acetylsalicylic acid [22] and was comparable with the effects observed after injection of 30 mg pentazocine [22] or 0.2 mg fentanyl [37] or after oral administration of 200 mg flupirtine [23]. However, there is a need to compare (R)-flurbiprofen directly with other non-opioid analgesics like paracetamol or with opioids.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, the chemo-somatosensory evoked potential (CSSEP) pain model has been successfully employed to quantify the effects of several central-acting analgesics [7]. Thus, the aim of the present study was to investigate the acute analgesic effectiveness of oral lamotrigine using the CSSEP pain model.…”
Section: Discussionmentioning
confidence: 99%